Lebanon-Weathering the Perfect Storms - Schimmelpfennig, Axel.; Gardner, E. (Washington, D.C. : International Monetary Fund, 2008)
This paper reviews Lebanon's ability to manage financial pressures following severe shocks despite its large public debt overhang and significant external vulnerabilities. Based on interviews with market participants in Beirut and London, the paper concludes that Lebanon's ability to weather what appear to be "perfect storms" derives from three characteristics: a perceived implicit guarantee from donors; Lebanon's track record of having never defaulted on external debt or deposits; and the unique market structure for Lebanese debt which is dominated by local banks and "dedicated" investors and depositors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet